H19 regulates the proliferation of bovine male germline stem cells via IGF‐1 signaling pathway. Issue 1 (1st August 2018) - Lei, Qijing; Pan, Qin; Li, Na; Zhou, Zhe; Zhang, Juqing; He, Xin; Peng, Sha; Li, Guangpeng; Sidhu, Kuldip; Chen, Shulin; Hua, Jinlian
Abstract : Self‐renewal and differentiation of male germline stem cells (mGSCs) provide the basic function for continual spermatogenesis. Studies of in vitro culture of germline stem cells are important and meaningful for basic biological research and practical application. Growth factors, such as GDNF, bFGF, CSF1, and EGF, could maintain the self‐renewal of mGSCs. Insulin‐like growth factor 1 (IGF‐1), an important growth factor, and its pathway have been reported to maintain the survival of several types of stem cells and play important roles in male reproduction. However, the mechanism through which the IGF‐1 pathway acts to regulate the self‐renewal of mGSCs remains unclear. We analyzed the effect of IGF‐1 on the proliferation and apoptosis of bovine mGSCs. We evaluated the expression profile of long noncoding RNA (LncRNA) H19 in bovine and mouse tissues. Moreover, we investigated whether LncRNA H19 could regulate the IGF‐1 pathway. Results showed that IGF‐1 could activate the phosphorylation of AKT and ERK signaling pathways, and the IGF‐1 pathway played an important role in regulating the proliferation and apoptosis of bovine mGSCs. The proliferation rate of mGSCs decreased, whereas the apoptosis rate of mGSCs increased when the IGF‐1 receptor (IGF‐1R) was blocked using the IGF‐1R‐specific inhibitor (picropodophyllin). LncRNA H19 could regulate the IGF‐1 signaling pathway and, consequently, the proliferation and apoptosis of mGSCs. The number of cells in the seminiferous tubule decreased when H19 was interfered by injecting a virus‐containing supernatant. Hence, LncRNA H19 participated in the regulation of the proliferation and apoptosis of mGSCs via the IGF‐1 signaling pathway. Abstract : In this study, we show that the IGF‐1 signaling pathway plays an important role in regulating the proliferation and apoptosis of bovine mGSCs, and LncRNA H19 regulates the IGF‐1 signaling pathway by influencing the expression of IGF‐1R.